The association of patients' daily summarized self‐rated "real‐time" pain scores with physical recovery after major surgery - A repeated measurement design - Lotta Wikström; Mats Nilsson; Kerstin Eriksson (Wiley, 2020)
Abstract Aim To determine the associations of patients' documented self‐rated pain with self‐rated early postoperative physical recovery. Design Observational with repeated measures. Methods General and orthopaedic inpatients (N = 479) were during the period 2012-2015 screened for pain. Individual daily median pain scores at rest and during activity were based on 4-9 self‐ratings on postoperative days 1 and 2, using the Numeric Rating Scale. Nine items reflecting physical recovery from the "Postoperative Recovery Profile" were used in a questionnaire. Results Associations between median pain scores on postoperative day 1 and physical recovery (fatigue, sleeping difficulties, bladder function, mobilization, muscle weakness and personal hygiene) the same day were found. Additionally, associations were found between median pain scores on day 1 and physical recovery (fatigue, sleeping difficulties, mobilization and muscle weakness) on day 2.